2021
DOI: 10.1101/2021.08.25.457649
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic drivers of large B-cell lymphoma resistance to CD19 CAR-T therapy

Abstract: Chimeric antigen receptor-reprogrammed autologous T cells directed to CD19 are breakthrough immunotherapies for heavily pretreated patients with aggressive B-cell lymphomas but still fail to cure most patients. Host inflammatory and tumor microenvironmental factors associate with CAR-19 resistance, but the tumor-intrinsic factors underlying these phenomena remain undefined. To characterize genomic drivers of resistance, we interrogated whole genome sequencing of 30 tumor samples from 28 uniformly CAR-19-treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 76 publications
1
8
0
Order By: Relevance
“…However, in a post hoc analysis of patients who had prior CD19‐directed therapies before receiving liso‐cel in TRANSCEND NHL 001, 92% achieved responses with no apparent effects on cellular kinetics 31 . Additionally, a study of genomic mechanisms involved in resistance to CAR T‐cell therapy in patients with LBCL found that neither reduced expression nor genomic alteration of CD19 was associated with poor outcomes 32 …”
Section: Discussionmentioning
confidence: 99%
“…However, in a post hoc analysis of patients who had prior CD19‐directed therapies before receiving liso‐cel in TRANSCEND NHL 001, 92% achieved responses with no apparent effects on cellular kinetics 31 . Additionally, a study of genomic mechanisms involved in resistance to CAR T‐cell therapy in patients with LBCL found that neither reduced expression nor genomic alteration of CD19 was associated with poor outcomes 32 …”
Section: Discussionmentioning
confidence: 99%
“…The circulating tumor DNA profiling of samples from r/r DLBCL patients who underwent CD19 CAR-T treatment determined the association of SOCS1 , TNFAIP3 , and XPO1 mutations with a poor prognosis after that therapy [ 117 ]. Additionally, the whole-genome sequencing analysis of CD19 CAR-T-treated large B cell lymphoma patients indicated some tumor intrinsic aberrations, such as RHOA or RB1 deletions, APOBEC mutational activity, and chromothripsis events as characteristics for relapsed patients [ 118 , 119 ]. The aforementioned defects were accompanied by preserved CD19 expression.…”
Section: Mechanisms Of Resistance To the Cd19 Car-t Therapy In B Cell...mentioning
confidence: 99%
“…DNA alterations included missense, deletion, frameshift, high-impact splice, and truncations. A GCB rrDLBCL validation cohort combining results from four sequencing studies was also assembled (N=54) [10][11][12][13].…”
Section: Data Collection and Nmf Clusteringmentioning
confidence: 99%
“…2C) [10]. We added cases to this rrDLBCL validation population, integrating Greenawalt, Morin (N=25), Juskevicius (N=21), and Jain (N=24) (Supplemental Table 6) [10][11][12][13]. Significant enrichment of TP53 alterations within GCB cases were noted for both rrDLBCL populations (Fig.…”
Section: Cohorts and Is Associated With Inferior Rchop Response Withi...mentioning
confidence: 99%